PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MATAHARI DEPARTMENT STORE MEDAN MALL - SARI PEBRINA; TOGU HARLEN LBN. RAJA; ARISMAN PARHUSIP (LP2MTBM MAKARIOZ, 2021)
This research was conducted to: (1) Knowing the promotion of products at PT Matahari Department Store Medan Mall, (2)Knowing the price of products at PT Matahari Department Store Medan Mall, (3) Knowing together (simultaneous)promotions and prices against purchasing decisions at PT. Matahari Department Store Medan Mall. This research is adescriptive quantitative method that uses numbers, ranging from data collection, interpretation of the data and theappearance of the results. The population in this study was the customers of PT Matahari Department Store Medan Mallduring the research. The sample size of the study taken by 80 people was determined by the sample technique used in thisstudy, namely random sampling (simple random sample) sampling technique is named so because in sampling, researchers